Comparing the disease course of patients with seronegative and seropositive rheumatoid arthritis fulfilling the 2010 ACR/EULAR classification criteria in a treat-to-target setting: 2-year data from the ARCTIC trial. Issue 2 (16th November 2018) - Nordberg, Lena Bugge; Lillegraven, Siri; Aga, Anna-Birgitte; Sexton, Joseph; Olsen, Inge Christoffer; Lie, Elisabeth; Berner Hammer, Hilde; Uhlig, Till; van der Heijde, Desirée; Kvien, Tore K; Haavardsholm, Espen A
Abstract : Objectives: Recent studies suggest that implementation of the 2010 American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) classification criteria for rheumatoid arthritis (RA) leads to higher inflammatory activity in seronegative compared with seropositive patients at time of diagnosis. Our aim was to compare the disease course in seronegative and seropositive patients classified according to the 2010 criteria. Methods: DMARD-naïve patients with RA fulfilling the 2010 criteria were included in the treat-to-target ARCTIC trial and followed for 24 months. We stratified patients as seropositive (rheumatoid factor (RF)+, anticitrullinated protein antibodies (ACPA)+ or both) or seronegative (RF– and ACPA–) and compared disease activity, radiographic progression, treatment response and remission rates across groups. Results: 230 patients were included with mean (SD) age 51.4 (13.7) years, and 61% were female. 34 patients (15%) were seronegative. At 24  months, disease activity measures, radiographic progression and remission rates were similar between groups, despite more inflammatory activity in seronegative patients at baseline. Treatment response was slower in seronegative compared with seropositive patients. The groups received similar treatment. Conclusion: Our findings suggest that among patients with RA classified according to the 2010 ACR/EULAR criteria, seronegative patients respond well to modern treatment strategies. However, treatment response was somewhat slower in seronegative patients and radiographic progression was similar in seronegative and seropositive patients. Our results indicate that seronegative RA is not a mild form of the disease and requires intensive treat-to-target therapy similar to treatment of seropositive RA.